The Rise of the Biomedical Sciences Master's Program at U.S. Medical Colleges. - Blanck, George (Teaching & Learning in Medicine)
Background:U.S. medical colleges commonly administer both M.D. and Ph.D. programs, but the value and application of these degrees are being challenged by economic developments.Summary: In medicine, the country faces a long-term period of cost cutting and new models for efficient healthcare delivery. In research, the outlook for the independently creative career is bleak, owing to the failure of the National Institutes of Health to engineer a sustainable program of scientists’ training and subsequent funding of the trained scientists’ research. However, an educational bright spot for medical colleges has been the biomedical science master's program.Conclusions: These programs have been highly popular with students and have the potential of reinvigorating the pool of student researchers, educating professionals in allied fields who are competent advocates for biomedical research, and providing professionals who can enter the healthcare delivery system with reduced expense, for example, as genetic or personalized medicine counselors.